Education for Sustainable Development in authoritarian contexts—Lessons from policy, practice and lived experiences in Belarusian schools - Sposab, Kate; Rieckmann, Marco; Pozniak, Alexandra (Frontiers in Education, 2025)
This study explores the implementation of Education for Sustainable Development (ESD) in Belarusian schools, focusing on changes before and after the 2020 political crisis. It examines the feasibility of ESD in a context marked by civic repression, centralized control, and the dismantling of civil society. A mixed-methods design was applied, combining Critical Discourse Analysis (CDA) of six national policy documents with content analysis of focus group interviews with teachers and students. Findings from the CDA show that Belarusian education strategies between 2016 and 2020 rhetorically aligned with the UN Sustainable Development Goals (SDGs). However, state discourse marginalizes civil society and non-formal education, while framing ESD narrowly as environmental literacy and health and safety education. Participation, inclusion, reflexivity, and the political dimension of sustainability—core elements in European ESD frameworks—are absent. Focus group interviews revealed that, despite these limitations, teachers drew on state education programs, local authority support, and “safe” ecological themes to maintain participatory and project-based learning. After 2020, these adaptive strategies were largely dismantled as civil society actors were dissolved, networks eroded, and ESD was reframed to serve ideological purposes. Educators reported profound transformative experiences, characterized by fear, psychological strain, and survival strategies such as avoiding controversial topics or working within discreet peer networks (“small circles”). This study underscores both the fragility and persistence of ESD in authoritarian contexts and calls for further research on how bottom-up educational practices can be supported without placing educators at risk.